Analisis Dampak Sedimentasi Terhadap Kapasitas Tampung Waduk di Jawa Tengah - Bina Arumbinang Wajdi; Ety Fitriyani; Hufa Istikomah; Abdul Fida Ismail (LPPM UNU CIREBON, 2025)
Reservoirs play a strategic role in supporting water security, providing raw water, agricultural irrigation, and flood control in Central Java. However, over the past two decades, sedimentation has become one of the most serious problems threatening the sustainability of reservoir functions. The accumulation of sediments on the reservoir bed gradually decreases storage capacity and reduces operational effectiveness, particularly during the dry season when water demand increases. This study aims to comprehensively examine the impact of sedimentation on reservoir storage capacity through literature analysis and secondary case studies. The method employed is a systematic literature review with a comparative analysis approach of several major reservoirs in Central Java, namely Wadaslintang, Kedungombo, Sempor, and Mrica. Secondary data were obtained from previous research, official reports from the River Basin Agency (BBWS), and national scientific publications. The results show that high sedimentation rates have reduced the effective storage capacity of reservoirs by 15-40 percent of their initial capacity. The main contributing factors include soil erosion in catchment areas, land-use changes, and limited maintenance activities. Therefore, an integrated sediment management strategy is required, combining technical measures such as dredging and sabo dams with non-technical approaches based on land conservation and community participation. This study is expected to serve as a reference for sustainable reservoir management planning in Central Java.